Pengaruh Premi dan Klaim Terhadap Keputusan Membeli Produk Asuransi Jiwa Syariah pada PT. Sunlife Financial Cabang Medan - Raihana, Rika; Syahriza, Rahmi (Universitas Labuhanbatu, 2021)
Healthy asset growth is considered as one of the foundations of the company's success. Among the internal factors that affect the growth rate of insurance company assets are premiums and claims. High premium receipts will provide the company with capital so that the company can invest to increase company and customer profits so that the company's assets continue to grow. Claims are indicated to reduce the company's asset growth because the higher the claim, the higher the company's expenses. The formulation of the problem in this study is how the influence of premiums and claims on the decision to buy sharia life insurance products at PT Sun Life Financial Medan Branch.